PARTISIPASI IBU-IBU JAMAAH PENGAJIAN YASINAN DALAM MENINGKATKAN KEPEDULIAN SOSIAL MASYARAKAT - Ratna Dwi Mei Wulandari; Sulistyo Anjarwati (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2018)
Community life has never been separated from social care. Social care is an interest or interest in helping others. The closest environment has a big influence in determining the level of social awareness. To increase the social sense, it can be through various activities, both religious activities and other activities. In this study the researchers focused more on religious activities, namely the activities of recitation of Yasinan. This research was conducted in Sumberjo Village, Sutojayan Sub-District, Blitar District. Data collection is done by interviews, documentation and observations in these activities. The results of the study indicate that the Yasinan Recitation Committee has activity agendas, ranging from the annual agenda to the agenda to be implemented. This activity is carried out on the basis of Islamic brotherhood which they believe can be intimately carried out by carrying out routine and structured religious activities and for the pilgrims to recite this sense of caring that is considered very important in carrying out Islamic teachings and fostering a sense of social care.